Re-negotiating space and place : intersections between migration and schooling in Kayamandi (Stellenbosch, Western Cape) - Combrink, Lize-Mare (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.